Groundwater flow in the Montea-Carpinoso hydrogeological unit (Calabria, Italy) - Fabbrocino, Sivia; Perrone, Fabio (Italian journal of engineering geology and environment, 2009)
This paper reports an outline of the conceptual model of flow in the carbonate unit formed by the Montea-Carpinoso Mountains (northern Calabria). The area is situated immediately to the north of the so-called "Sangineto line", which marks the interface between the Apennine chain carbonate domains and the crystalline-metamorphic units of the Calabrian Arc. Its consequent geological and tectonic evolution significantly influenced the surface hydrography and split up the groundwater flow. It is worth noting that within the context of the current study, monthly monitorings (March 2005-October 2006) of 15 springs were carried out. Springs are spread along the western edge with an average discharge which ranges between 28 and 165 l/sec, all fed by the basal groundwater flow albeit, divided largely into two distinct groundwater basins. As well as the springs, increases in the discharges of the major streams were recorded, in particular in the northern basin, where their course coincides with significant tectonic alignments. Indeed, in the case of the Vaccuta stream, as a result of the mentioned tectonization of the carbonate rocks, a phenomenon of reinfiltration of the waters to the point of near extinction of the surface flow was observed.The different geo-morphological and geodynamic evolution of the carbonate massif of Calabria, compared with those which are well documented in other areas of southern Italy, have in fact strengthened the condition of flow through the interconnected fracture network.